qEEG study on Reading Quranic verse 36 ‘Yasin’ and Malay Language - Norsiah, Fauzan; Muhammad Sophian, Nazarudin; Ahmad Sofian, Shminan; Ida Juliana, Hutasuhut; Merikan, Aren; Syifaa, Mohd.Sabri (2018)
Abstract- This article reports the study on the brainwaves patterns between the activity of reading the Arabic and reading Malay text among the final year undergraduates in the university of Malaysia Sarawak. Three students volunteered for the research and their brain waves were observed and recorded to find out the difference of brainwave pattern while reading Arabic and Malay language. The observation showed a dominant production of delta followed by theta while reading Arabic and Malay language. The text used for reading were from Verse 36 (Arabic and the translated version in Malay ) of the Quran. The average mean of delta wave were higher for the reading of Arabic language at the frontal lobe than while reading the Malay translation. The frequency of delta rhythm of the Arabic language differed from the Malay language due to the nature of the Arabic language. The neural circuits of the rhythm from the Arabic recitation implicates not on just the spatial visual area at the parietal lobe but also the visual eye movement at the frontal region guided by the Visual system at the Medial temporal area.